PERBEDAAN PEMBOBOTAN T2 TURBO SPIN ECHO (TSE) MRI BRAIN POTONGAN AXIAL ANTARA PENGGUNAAN SENSITIVITY ENCODING (SENSE) DENGAN TANPA SENSE : EVALUASI PADA SIGNAL TO NOISE RATIO (SNR) DAN SCAN TIME - Fani Susanto; Gunawan Santoso; Bagus Abimanyu (Perhimpunan Radiografer Indonesia (PARI), 2018)
Backgroud: MRI examination of brain often find patients who are less cooperative, thus requiring rapid acquisition techniques. Parallel imaging technique sensitivity encoding (SENSE) utilizing the spatial information RF coil phased array to reduce the acquisition time by reducing the number of sampling lines K space therefore produce quality and good spatial resolution, but its has the limitations, namely the reduction of signal to noise ratio (SNR). SENSE is used along with pulse sequence one of turbo spin echo (TSE). The purpose of this research was to determine the differences in SNR and scan time on T2 weighted TSE MRI of brain axial slices between use SENSE with no SENSE. Methods: This research is a quantitative study with an experimental approach. Data were collected from May to June 2016 in Radiology Unit Premier Bintaro Hospital by calculating the SNR value through software for the region of interest (ROI) and calculate the scan time through the scan timer on the workstation monitor. Data was analyzed by statistical tests with SPSS 16 software using paired T-test and descriptive. Results: From the statistical test result known that the SNR on T2 TSE between use SENSE with no SENSE the p-value 0,000 (p <0,05). This is because the encoding between the two images are different, the image of the T2 TSE without SENSE contained use of pulses in 1800 approached TE effectively so shallow gradients produce echo maximum, while the image of the T2 TSE using SENSE there is a reduction in line phase encoding in the K space and their g-factor causing reduced SNR. From the analysis descriptively known that the scan time on T2 TSE between use SENSE with no SENSE by reducing scan time for 1 minute 24 seconds (49,01%). This is because the acquisition techniques are different between the two images, the image without SENSE T2 TSE contained ETL in the filling K space, while the T2 TSE images using SENSE R-factors are causing sampling did not fill all the K space so that the scanning time is reduced. Conclusion: There is a difference in SNR and scan time of T2 weighted TSE MRI of brain axial slices between use SENSE with no SENSE